Personal Assistants: Emerging Computational Technologies (Cham : Springer International Publishing, 2018)
This book provides an overview of the current research in the interdisciplinary area of personal assistants (PA) and cognitively inspired systems. It discusses the most relevant topics in this highly diversified domain, like reasoning, health, personalization, robotics, and ethical and social issues. Personal assistants (PA) are a relatively new concept directed at people with cognitive or physical disabilities, and is expanding to include complex platforms such as sensors, actuators, monitoring abilities and decision processes. Designed for a general audience, it is also of interest to undergraduates, graduates and researchers involved with intelligent systems, ambient intelligence or ambient assisted living. The content goes from an introduction of the field (aimed at undergraduates and a general readership) to specific and complex architectures (aimed at graduates and researchers).
A Survey of Cognitive Assistants -- Argumentation-based Personal Assistants for Ambient Assisted Living -- Kidney Care - A Personal Assistant Assessment -- Personalized Assistant for Cognitive Training of the Elderly -- Personal Robot Assistants for Elderly Care: An Overview -- Personalized Visual Recognition via Wearables: A First Step toward Personal Perception Enhancement -- Intelligent personal assistant for educational material recommendation based on CBR -- An Overview to Human-Robot Interaction -- Bilateral trust-based collaboration between a physical robot and a virtual human through a unified platform for personal assistance to humans -- Emotion Detection and Regulation from Personal Assistant Robot in Smart Environment -- EDI for Consumers, Personal Assistants and Ambient Intelligence- The right to be forgotten -- Personal Assistants: Civil Liability and Dispute Resolution.
Engineering
text file PDF
Keywords: Computational intelligence; Artificial intelligence